Managers' view: the marketing strategies adopted by agricultural stores (Research, Society and Development, 2020)
The objective of the study was to analyze the marketing strategies adopted by agricultural stores in the municipality of Três de Maio - RS. The methodology used was the deductive method, the interview technique and the observation in data collection. The analysis used content analysis, descriptive and comparative statistics. It was interviewed, 15 managers of 17 existing agricultural stores and identified in the urban perimeter of the municipality under study. For 73% of respondents, location is an extremely important factor in the process of marketing inputs and 93% of stores carry out loyalty practices, such as differentiated discounts for old customers or those who purchase a larger volume of inputs. In legal matters, mainly related to environmental aspects, about 50% of stores need adjustment. The results obtained allow us to affirm that the majority of agricultural stores are aligned with their customers (producers), minor adjustments are necessary regarding the marketing strategies adopted.